Single-stranded fraction of deoxyribonucleic acid from Bacillus subtilis. - Piwnicka, M (1981)
About 13% of the deoxyribonucleic acid (DNA) of various strains of Bacillus subtilis, independent of the stage of growth or competence for transformation, was rendered acid soluble by endonuclease S1. In a pH 11.2 CsCl gradient, 4% of the untreated DNA banded at the density typical for single-stranded molecules, whereas 9% of the remaining DNA (main band) was sensitive to endonuclease S1. Selective inhibition of DNA polymerase III, or of DNA-dependent ribonucleic acid polymerase, did not increase or abolish single-strandedness. The DNA purification procedure did affect the level of single-stranded DNA, indicating its binding to cell constituents containing ribonucleic acid, protein, and membranous material. The molecular weight of the single-stranded fraction resembled that of total denatured DNA, and its buoyant density in an alkaline CsCl gradient was centered partially at a density of 1.772 g/cm3 and partially at a density of 7.759 g/cm3. Incubation of DNA under conditions leading to renaturation of its single-stranded fraction led to an increase in transforming activity for the purA16+ marker (close to the origin of replication) relative to leu-8+ and metC3+ markers (located in the middle of the chromosome), indicating this region is the main source of the single-stranded fraction.